2005
DOI: 10.1074/jbc.m410917200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ca2+-dependent Desensitization in the Vanilloid Receptor TRPV1 by Calcineurin and cAMP-dependent Protein Kinase

Abstract: The vanilloid receptor TRPV1 is a polymodal nonselective cation channel of nociceptive sensory neurons involved in the perception of inflammatory pain. TRPV1 exhibits desensitization in a Ca 2؉ -dependent manner upon repeated activation by capsaicin or protons. The cAMP-dependent protein kinase (PKA) decreases desensitization of TRPV1 by directly phosphorylating the channel presumably at sites Ser 116 and Thr 370 . In the present study we investigated the influence of protein phosphatase 2B (calcineurin) on Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
225
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(245 citation statements)
references
References 33 publications
15
225
1
1
Order By: Relevance
“…38 In contrast, phosphorylation by protein kinase A and protein kinase C has been proposed to slow desensitization in TRPV1 channels, 39,40 and protein kinase C has also been implicated in reversing desensitization of TRPM4 channels. 41 Ca 2+ /CaM regulated phosphorylation/dephosphorylation has also been proposed: phosphorylation of TRPC5 by myosin light chain kinase is associated with slowing of desensitization 42 and dephosphorylation of TRPV1 by calcineurin is reported to promote desensitization.…”
Section: Mechanism-ca 2+ -Regulated Kinases and Phosphatasesmentioning
confidence: 99%
“…38 In contrast, phosphorylation by protein kinase A and protein kinase C has been proposed to slow desensitization in TRPV1 channels, 39,40 and protein kinase C has also been implicated in reversing desensitization of TRPM4 channels. 41 Ca 2+ /CaM regulated phosphorylation/dephosphorylation has also been proposed: phosphorylation of TRPC5 by myosin light chain kinase is associated with slowing of desensitization 42 and dephosphorylation of TRPV1 by calcineurin is reported to promote desensitization.…”
Section: Mechanism-ca 2+ -Regulated Kinases and Phosphatasesmentioning
confidence: 99%
“…Notably, both PKA phosphorylation sites as well as putative SNARE interaction sites are located on the N-terminal of TRPV1 (8,47,48), such that phosphorylation of TRPV1 by PKA could lead to enhancement of these exocytosis pathways through to-date unknown mechanisms. Indeed, PKA-dependent trafficking pathways have been reported for a number of receptors and ion channels including the chloride-selective anion channel CFTR and AMPA receptor (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was confirmed with de facto electrophysiological data by Fomina and Levitan who demonstrated that in rat pituitary lactotrop cells inhibition of CaN activity by CsA has led to reduced ionic currents via voltage-gated Ca 2+ channels [91]. Since then, CaN has been shown to modulate a number of ion channels including inhibition of the arachidonate-regulated Ca 2+ channels (ARC channels that are closely related to the store-operated CRAC channel Orai proteins) [92]; the intracellular Ca 2+ release channels inositol trisphosphate receptor (IP 3 R) and ryanodine receptor (RyR) [61]; or the vanilloid receptor TRPV1 [93]. In smooth muscle cells, PP1 was described to increase the open probability of the large-conductance, voltage-and Ca 2+ -gated K + (BK Ca ) channel; in contrast, PP1 inhibited the A-type K + channel 19-pS in mouse colon cells through its fast inactivation mechanism.…”
Section: Regulation Of Ion Channel Functions and Ca 2+ Homeostasis Bymentioning
confidence: 99%